2014
DOI: 10.1179/1476830514y.0000000115
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and pleasantness of sucrose taste in patients with winter depression

Abstract: The present results suggest that: (i) winter depression is not associated with major alterations in gustatory function; and (ii) sweet craving and increased consumption of carbohydrates in patients with winter depression is not secondary to altered responses to sweet tastants. More studies are needed to characterize hedonic responses of patients with SAD to other sweet and non-sweet foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Although lever pressing was lower in cH rats compared to the other groups, it increased across the extinction sessions in correspondence with an increase in reinforcer value. This further supports the idea that cH rats are capable of estimating the hedonic value of the reinforcer, consistent with the prevailing literature which suggests normal hedonic estimates in depressed patients (Berlin et al, 1998;Scinska et al, 2004;Swiecicki et al, 2009Swiecicki et al, , 2015Clepce et al, 2010). In fact, when changes were found, depressed patients rated olfactory stimuli as more pleasant (Pause et al, 2001;Lombion-Pouthier et al, 2006), and also reported increased cravings of sweets and carbohydrates (Moller, 1992).…”
Section: Discussionsupporting
confidence: 88%
“…Although lever pressing was lower in cH rats compared to the other groups, it increased across the extinction sessions in correspondence with an increase in reinforcer value. This further supports the idea that cH rats are capable of estimating the hedonic value of the reinforcer, consistent with the prevailing literature which suggests normal hedonic estimates in depressed patients (Berlin et al, 1998;Scinska et al, 2004;Swiecicki et al, 2009Swiecicki et al, , 2015Clepce et al, 2010). In fact, when changes were found, depressed patients rated olfactory stimuli as more pleasant (Pause et al, 2001;Lombion-Pouthier et al, 2006), and also reported increased cravings of sweets and carbohydrates (Moller, 1992).…”
Section: Discussionsupporting
confidence: 88%
“…This stands in direct contrast to the fairly consistent effect of age on sweet-liking whenever children or adolescents were compared with adult populations [101,102,103,104], and may be due to the relatively restricted age range tested here. To note, in some [13,16,74,76,78,105,106,107,108] but not all [13,81,109,110,111] studies testing middle-aged or older adults, SDs and those with an inverted U-shaped response outnumbered SLs. Critically, methodological limitations that may lead to possible overestimation of the SD phenotype in prior studies cannot also be overlooked [11].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, no differences were observed [112]. Patients suffering from depression showed no differences in their sweetness preference when compared with individuals who were not suffering from depression [111,113]. In anorexic restrictors, there was a significantly lower preference for the least sweet sucrose solutions when compared to healthy controls and anorexic bulimics.…”
Section: Studies In Subjects With a Neurological Or Psychological Dismentioning
confidence: 91%
“…Twelve studies were identified wherein the effects of disease on sweetness preference were investigated (Table S3-11 of Supplementary File S3). Seven of the studies included subjects with a neurological or psychological disease [108][109][110][111][112][113][114], three included subjects with type 2 diabetes mellitus (T2DM) or gestational diabetes mellitus (GDM) [115][116][117], and two included subjects with other diseases, namely end-stage renal disease or Prader-Willi Syndrome (PWS) [118,119]. All studies but one were conducted in adults.…”
Section: Disease and Sweetness Preferencementioning
confidence: 99%